The association between mobile game addiction and mental health problems and learning outcomes among Thai Youths classified by gender and education levels - Chakkraphan Phetphum; Orawan Keeratisiroj; Atchara Prajongjeep (Wolters Kluwer Medknow Publications, 2023)
Introduction: Youth are increasingly playing mobile games, which are distinct from traditional games, but there is limited research investigating the causal relationship between mobile game addiction and mental health problems in Thailand. This study investigated the association between mobile game addiction and depression, loneliness, and social anxiety as well as academic performance. Methods: In this cross-sectional study, data were collected from 3427 students in Thailand from May to September 2022, using a 5-part self-report questionnaire. A multistage random sampling was performed. Descriptive statistics and structural equation modeling (SEM) were used to analyze the data. Results: The prevalence of mobile game addiction among Thai youth was 22.2% (95% confidence interval = 20.9-23.7), which was higher among females (25.6%) than males (17.9%) with P < 0.001 and higher among high school students (25.6%) than vocational (20.6%) and undergraduate students (20.0%) with P = 0.001. According to the SEM analysis, mobile game addiction was significantly associated with depression (β = 0.36, P < 0.001), loneliness (β = 0.31, P < 0.001), social anxiety (β = 0.28, P < 0.001), and grade point average mediated by social anxiety (β = 0.10, P < 0.001). Conclusion: The model depicting the causal relationship between mobile game addiction, depression, loneliness, social anxiety, and academic performance is consistent with empirical data. The identification of a substantial group of addicted mobile gamers and the addiction effects on mental health issues supports efforts by all stakeholders to prevent youth from becoming game addicted as well as treat addicted gamers.